Longitudinal Gradient of Nitrate (NO 3 - ) And Phosphate (PO 4 3- ) In Air Hitam River Pekanbaru City - Mike Satriani; Asmika Harnalin Simarmata; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTLongitudinal Gradient of nitrate (NO 3 - ) and phosphate (PO 4 3- ) in Air Hitam River was carried out in September 2021. This study aims to determine the Longitudinal Gradient of nitrate and phosphate in the Air Hitam River Pekanbaru City. There were 5 stations, namely Station 1 (upstream), Station 2, 3, 4 (in the middle of river), Station 5 (down stream).  Sampling was done 3 times, once/3 days.  Water quality parameter were measured such as nitrate and phosphate (main parameter) and temperature, transparency, pH, dissolved oxygen, BOD 5 , and free carbondioxide.  Result shown nitrate concentration ranges from 0.1861-0.03181 mg/L, phosphate ranges from 0.2662-0.3208 mg/L, temperature ranges from 28-29ºC, pH ranges from 5.5-6, transparency : 18-28 cm, dissolved oxygen (DO) ranged 6,10-6,18 mg / L, free carbon dioxide (CO 2 ) ranged : 7,99 - 9,32 mg / L, BOD 5  ranged 5,5-6,0 mg /L. The longitudinal gradient of nitrate and phosphate does not show a characteristic pattern in the Air Hitam River. Based on the phosphate concentration, the trophic status of the Air Hitam River is hypereutrophicKeywords: nitrate and phosphate longitudinal gradient, water quality, Air Hitam River